Some aspects of the development of the relationship institute of citizenship and youth in Uzbekistan - Shukhrat Mamatkulov (International Consortium of Education and Culture Research Studies, 2019)
This article highlights some aspects of improving the interaction of civil society institutions with young people in the implementation of youth policy and strategy of Uzbekistan, as well as ensuring their activity in political life.Social requests related to the increase of social activity of young people were also presented.